2017
DOI: 10.15252/emmm.201606773
|View full text |Cite
|
Sign up to set email alerts
|

Loss of AXIN1 drives acquired resistance to WNT pathway blockade in colorectal cancer cells carrying RSPO 3 fusions

Abstract: In colorectal cancer (CRC), WNT pathway activation by genetic rearrangements of RSPO3 is emerging as a promising target. However, its low prevalence severely limits availability of preclinical models for in‐depth characterization. Using a pipeline designed to suppress stroma‐derived signal, we find that RSPO3 “outlier” expression in CRC samples highlights translocation and fusion transcript expression. Outlier search in 151 CRC cell lines identified VACO6 and SNU1411 cells as carriers of, respectively, a canon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 52 publications
8
23
0
Order By: Relevance
“…A potential strategy to trigger the β-catenin pathway is inhibition of Axin1. Picco et al showed that targeting Axin1 with the porcupine inhibitor LGK974 was a potential approach for the treatment of colorectal cancer (Picco et al, 2017). Chimge and colleagues reported that RUNX1-mediated Axin1 suppression led to the activation of β-catenin (Chimge et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A potential strategy to trigger the β-catenin pathway is inhibition of Axin1. Picco et al showed that targeting Axin1 with the porcupine inhibitor LGK974 was a potential approach for the treatment of colorectal cancer (Picco et al, 2017). Chimge and colleagues reported that RUNX1-mediated Axin1 suppression led to the activation of β-catenin (Chimge et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although clear sensitivity to the Porcupine inhibitor LGK974 was observed in vitro and in vivo in a murine xenograft model, long-term treatment led to the emergence of a resistant population. This resistant population was characterized by two novel frame-shift deletions in AXIN1 , resulting in protein loss [ 143 ]. Although no mutations in Wnt pathway components in MM have been reported, treatment of the active Wnt signaling pathway can thus result in emergence of such mutations.…”
Section: The Wnt Pathway As a Potential Therapeutic Target In Multiplmentioning
confidence: 99%
“…Anti-tumor activity in RSPO3 fusion containing CRC tumors has been reported with another RSPO3 neutralizing antibody 14 . Two CRC cell lines, VACO6 and SNU1411, have been identified which have PTPRK-RSPO3 fusions, overexpress RSPO3 and are sensitive to porcupine inhibition 20 . The VACO6 xenograft model demonstrates tumor growth inhibition when exposed to anti-RSPO3 alone or in combination with the topoisomerase inhibitor irinotecan or alternatively in combination with nab-paclitaxel (Fig.…”
Section: Introductionmentioning
confidence: 99%